STUDYING TO PROTECT AND MANAGE ENVIRONMENT IN MATARAM TOWN - Sosman, Arya (Jurnal IUS (Kajian Hukum dan Keadilan), 2014)
In Environment and room design are two things are different but it has iteralated each other room designing is the instrument for all development the activities which is affiaring of over on mean that is very high risk lately. Indonesian government through the institution No. 32 in 2009,Â  that is about PPLH was included the principle of international agreement,Â  beside that the institution No. 26Â  in 2007 about room designing which have a lot of contribution on room designing that it could be avoided the environment crush,Â  the local rules No. 12 in 2011 about RT, RW of Mataram town as the key of the room designing implementation with the theoretically mustÂ  be synchronised with the both of institution above. Beside that the local rules of RT, RW Mataram town must be harmonized with local rules which the related to the local rules of the environments formula of the problem which is proposed are: 1. How are the synchronised and harmonizations between local rules of RTRW Mataram town with UUPLH and Mataram town rules environment. 2. How is implementation of local rules of RTRW Mataram town particularly related to environments. This research is used normative-empiric approaches. This research ued turn (Stufen bau Theory),Â  autority theory,Â  low invorsment theory,Â  normally theory and effectively theory and also supported by material low citizen and welfare theory. Based on the analyses,Â  researcher concluded that there is existent in insincronisation between local rules no 12 in 2011 about RTRW Mataram town with the local rules No. 3 in 2010 about RTRW west Nusa Tenggara province on RT H. Also between local rules No. 5 in 2014 about UKL/UPL were disharmony. Otherwise if it is reviewed intensively between local rules RTRW ofÂ  Mataram town with the institution No. 32 in 2009 about PPLH and institution No. 26 in 2007 about room designingÂ  were existed synchronized of all principle,Â  purposes philosophy and disubstancial of rules. Means while,Â  the implementation of local rules of RTRW Mataram town can be concluded a part of local rules was implemented. It was accurate because there is no local rules on RDTRK. The government of Mataram town is just now meet the target of RTH about 1.606, 51 hectare or about 26.86 percent from 1.839 hectar (30%). In order to meet the target the government of Mataram town do some programs such as âgreen cityâ,Â  etc.Key Words: Protection and Managing of Environment,Â  Room Designing Mataram Town.